Effects of Socioeconomic Status on Physical and Psychological Health: Lifestyle as a Mediator - Wang, Jian; Geng, Liuna (International journal of environmental research and public health, 2019)
Health is correlated to people’s socioeconomic status (SES) and lifestyle. This study examined the impact of SES on respondents’ physical and psychological health. Moreover, we explored the potential mediating effect of lifestyle on the relationship between SES and health. The participants were 986 respondents from the 2015 Chinese General Social Survey (CGSS). Structural equation modeling (SEM) was used to test the hypothesized relationship between the variables. The results indicated that SES had a significant impact on people’s physical health, but the impact of SES on psychological health was not significant. Lifestyle had significant positive effects on both physical and psychological health. In addition, lifestyle mediated the relationship between SES and health. This research is helpful in gaining a better understanding of the relationship and mediating mechanism between SES, lifestyle, and health. It is recommended that research with longitudinal design and comprehensive indicators be undertaken in the future.